Implementing an “Impracticable” Copolymerization to Fabricate a Desired Polymer Precursor for N-doped Porous Carbons - Qi, Shi-Chao; Lu, Xiao-Jie; Lou, Yin-Cong; Zhou, Rui; Xue, Ding-Ming; Liu, Xiao-Qin; Sun, Lin-Bing (Engineering (Beijing, China), 2022)
It is common that a proof-of-concept of a desired reaction, which might generate materials with new functions or application potential, is eventually proved impracticable or commercially unfeasible. Considerable efforts have been made but wasted in searching for unknown reaction conditions in solvent environments because it was believed that the activity of reactants can be enhanced to facilitate reactions by dissolving them in solvents. However, an abnormal case was discovered in this study. A desired copolymerization reaction between 1,3,5-tris(chloromethyl)-2,4,6-trimethylbenzene and melamine was confirmed to be impracticable under various solvent conditions; however, it was successfully implemented using a solvent-free method. Using first-principle calculations and molecular dynamics simulations, two decisive factors that the reaction in solvents cannot possess, namely the reaction equilibrium being pushed by the timely release of by-products and the confined thermal motions of the activated monomer molecules in the solid phase, were demonstrated to make the copolymerization successful in the solvent-free method. Owing to the high aromaticity and azacyclo-content, the as-synthetic copolymer exhibited good application potential as a precursor to fabricate N-doped porous carbons with satisfactory carbon yields, ideal N contents, desired textural properties, and competitive CO2 capture abilities compared to other representative counterparts reported recently.